2016
DOI: 10.1038/srep36136
|View full text |Cite
|
Sign up to set email alerts
|

A Presenilin/Notch1 pathway regulated by miR-375, miR-30a, and miR-34a mediates glucotoxicity induced-pancreatic beta cell apoptosis

Abstract: The presenilin-mediated Notch1 cleavage pathway plays a critical role in controlling pancreatic beta cell fate and survival. The aim of the present study was to investigate the role of Notch1 activation in glucotoxicity-induced beta cell impairment and the contributions of miR-375, miR-30a, and miR-34a to this pathway. We found that the protein levels of presenilins (PSEN1 and PSEN2), and NOTCH1 were decreased in INS-1 cells after treatment with increased concentrations of glucose, whereas no significant alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…miR-34a/NOTCH1 signaling is also reported to promotes osteogenic differentiation of human adipose-derived stem cells (hASCs) via a coregulatory network [27]. Our study also indicated that overexpression of miR-34a induced the downregulation of NOTCH1 in vascular endothelial cells, which has been identified as a target gene of miR-34a in tumor cells, hASCs, RAW264.7 cells and pancreatic beta cell [24,[26][27][28]. In a pilot cross-sectional study, circulatory miR-34a is significantly elevated in diabetic patients compared with healthy controls [29].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…miR-34a/NOTCH1 signaling is also reported to promotes osteogenic differentiation of human adipose-derived stem cells (hASCs) via a coregulatory network [27]. Our study also indicated that overexpression of miR-34a induced the downregulation of NOTCH1 in vascular endothelial cells, which has been identified as a target gene of miR-34a in tumor cells, hASCs, RAW264.7 cells and pancreatic beta cell [24,[26][27][28]. In a pilot cross-sectional study, circulatory miR-34a is significantly elevated in diabetic patients compared with healthy controls [29].…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that the miR-34a/NOTCH1 signaling pathways mediate glucotoxicity-induced pancreatic beta cell apoptosis [24].…”
Section: Mir-34a Mimics/inhibitors Injection Regulated Notch1 Expressmentioning
confidence: 99%
“…Epigenetic mechanisms may also contribute to gluco(lipo)toxicity-induced beta-cell apoptosis by modulating gene expression through chromatin modification and/or non-coding RNAs. Indeed, Li et al demonstrated that the microRNAs (miRNAs) miR-375, miR-30a and miR-34a are increased in INS-1 cells and pancreatic islets exposed to high glucose levels, as well as in islets from diabetic GK rats [ 133 ]. miRNAs are endogenous non-coding RNAs known to regulate gene expression by binding to the 3′UTR of their target mRNAs resulting in their degradation and/or translational inhibition.…”
Section: Molecular Mechanisms Involved In Beta-cell Apoptosismentioning
confidence: 99%
“…Bioinformatics prediction. Previous studies have reported that a number of miRs are involved in regulating the occurrence and progression of T2DM (12)(13)(14)(15)(16). To further determine whether THBS-1 is regulated by other molecules in its actions on the lipotoxicity of INS-1 cells, miRanda, Targetscan and PicTar were used to predict the possible miRs that may target THBS-1.…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs (miRs) are 19 to 22-nucleotide noncoding RNAs that can regulate cell survival, cell function, apoptosis and differentiation by suppressing the transcription of mRNA (11)(12)(13). Currently, extensive research has suggested that miRs are involved in fatty acid-induced beta cell dysfunction (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%